Diversity of antibiotic resistance genes in soils with four different fertilization treatments - Wang, Zhuoran; Zhang, Na; Li, Chunming; Shao, Liang (Frontiers in Microbiology, 2023)
Although the enrichment of resistance genes in soil has been explored in recent years, there are still some key questions to be addressed regarding the variation of ARG composition in soil with different fertilization treatments, such as the core ARGs in soil after different fertilization treatments, the correlation between ARGs and bacterial taxa, etc.For soils after different fertilization treatments, the distribution and combination of ARG in three typical fertilization methods (organic fertilizer alone, chemical fertilizer alone and conventional fertilizer) and non-fertilized soils were investigated in this study using high-throughput fluorescence quantitative PCR (HT-qPCR) technique. The application of organic fertilizers significantly increased the abundance and quantity of ARGs and their subtypes in the soil compared to the non-fertilized soil, where sul1 was the ARGs specific to organic fertilizers alone and in higher abundance. The conventional fertilizer application also showed significant enrichment of ARGs, which indicated that manure addition often had a more decisive effect on ARGs in soil than chemical fertilizers, and three bacteria, Pseudonocardia, Irregularibacter, and Castllaniella, were the key bacteria affecting ARG changes in soil after fertilization. In addition, nutrient factors and heavy metals also affect the distribution of ARGs in soil and are positively correlated.